Analysis of a Malaysian edition of foreign magazines in portraying women's issues - Alagappar, Ponmalar N.; Selvaratnam, Lavanya (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2014)
In the last 20 years there has been an influx of women magazines in the market and its fast becoming a popular media that is widely read by women of all ages.Most magazines have a specific target audience, often a particular age and gender group attached to a hobby, interest or lifestyle. Magazines unlike books offer “light reading” thus sustaining the interest of the reader and has a relatively longer shelf life.Magazines are perhaps one of the most powerful educational forces in society.Women and teenage girls are becoming dependent on these magazines for guidance and advice which only reinforces their belief on what is accepted by society.For many women and teenage girls, these magazines play an important socializing function through the stories they tell in their contents and worth, love and sexuality, popularity and normalcy.In a mediated society, audience receives more information from the media rather than from textbooks, schools and family about sex (Haryati, 2008).This paper examines how women issues are portrayed in local edition of a foreign magazine in terms of choice of content and advertisement.What do these publications communicate to women about gender and gender roles? It is undeniable that communication is extremely important for women’s development and mass media play significant role in communication. It is to be noted that growth of women’s education and their entry into employment has contributed to the growth of media and vice versa.It is true that media has brought to light, as never before, certain misdemeanours against women which have helped in progress of women but in a very subtle manner it also perpetuated the stereotyped image of woman as a householder and an inconsequential entity in the traditional value system.Have the changes of representation of women over the period of time only opened doors for single women? Or does it confirm to some of the traditional notions about married women and their role in society? That is the question we wish to deal with in this paper.The objective of this study is to examine a local edition of a foreign Malaysian women’s magazine which appeals to homemakers on role portrayals of women in organizations.